تقييم مدى تطبيق سياسات تسويقية تستند على إدارة التكاليف التسويقية في المصارف الخاصة في مدينة اللاذقية - ياسين, أيام (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تهدف هذه الدراسة إلى بيان مدى تطبيق المصارف الخاصة في سورية لإدارة التكاليف التسويقية ضمن خططها التسويقية المطبقة, فركزت على المعرفة بمفهوم التكاليف التسويقية ومقومات تطبيقها ومدى تطبيق هذه المقومات في سياساتها التسويقية، ومدى التخطيط والقياس لتكاليف الأنشطة التسويقية وتوجيه الخطط باتجاه تخفيض التكلفة دون تأثر الأداء ورضا العملاء. واعتمد ذلك على استخدام المنهج الوصفي من خلال تصميم استبانه وتوزيعها على بعض العاملين في المصارف الخاصة, كما تم تحليل البيانات باستخدام البرنامج الإحصائي SPSS ، وتوصلت الدراسة إلى أن المقومات الأساس لإدارة تكاليف التسويق غير مطبقة بشكل يحسن من الأداء في المصارف، وأن المصارف لا تراعي إدارة فعالة للتكاليف من خلال أنشطة التسويق المطبقة لديها.The research aims to show the extent of application of marketing cost management in Syrian private banks’ marketing plans. So, it has focused on understanding the concept of marketing costs, their application elements, the extent of the application of these elements in their marketing policies, and the extent of planning and measurement of marketing activities costs and make a plan that contributes to cost reduction without impinging on performance or customer satisfaction.The researcher depended on descriptive approach in the research community and a survey has been designed and distributed among some employees in private banks, then the researcher analyzed the survey results by the Statistical Package for the Social Sciences (SPSS).The research concluded that there wasn’t a good application of marketing cost management costs in a way that helps improve banking performance and the banks does not take cost effective management into account through marketing activities they have